2020
DOI: 10.3390/jpm10040237
|View full text |Cite
|
Sign up to set email alerts
|

The Road so Far in Colorectal Cancer Pharmacogenomics: Are We Closer to Individualised Treatment?

Abstract: In recent decades, survival rates in colorectal cancer have improved greatly due to pharmacological treatment. However, many patients end up developing adverse drug reactions that can be severe or even life threatening, and that affect their quality of life. These remain a limitation, as they may force dose reduction or treatment discontinuation, diminishing treatment efficacy. From candidate gene approaches to genome-wide analysis, pharmacogenomic knowledge has advanced greatly, yet there is still huge and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 161 publications
(178 reference statements)
0
2
0
Order By: Relevance
“…In line with this, Simoes et al suggested that chemotherapy-induced toxicity in colorectal cancer is likely complex and multigenic [7]. For this reason, they summarized the pharmacogenomic data on colorectal cancer, including candidate gene approaches, genome wide association studies, and next-generation sequencing studies.…”
mentioning
confidence: 98%
“…In line with this, Simoes et al suggested that chemotherapy-induced toxicity in colorectal cancer is likely complex and multigenic [7]. For this reason, they summarized the pharmacogenomic data on colorectal cancer, including candidate gene approaches, genome wide association studies, and next-generation sequencing studies.…”
mentioning
confidence: 98%
“…It has been reported that of mCRC patients treated with FOLFOX, FOLFIRI, or XELOX, nine in ten will experience at least one adverse drug reaction, and two-thirds will have one or more adverse events during the first line of treatment. Such events and the interventions to resolve them further increase the economic burden on the patient [ 12 ]. In LMICs, the cost of treatment is more often than not borne by the patient, in contrast to patients in upper- and upper-middle-income countries where treatment is covered [ 13 ].…”
mentioning
confidence: 99%